Penerapan Konsep Kaizen Untuk Menurunkan Lead Time Express Maintenance Pada PT Indomobil Trada Nasional Depok - Adiyoso Putro, Ismail (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
Consistency of the quality of a service will affect the survival or lack of such a company in the needs of a very diverse market, so an effort is needed in the management of the company with control and improvement of quality. Kaizen is one way of continuous improvement that involves everyone both managers and employees to get optimal results. The purpose of the research is to identify any obstacles that occur in the process of working on express maintenance as well as to find the right and good solution to lower lead time in express maintenance. Then kaizen concept was applied to lower lead time express maintenance at PT Indomobil Trada Nasional. There are some problems: the creation of old spare parts, indirect parking fittings, incomplete tools, neatly arranged tools, and irregular workflows. After improvement, lead time express maintenance dropped from each work, PMS 10,000 KM dropped 8 minutes, PMS 20,000 KM dropped by 12 minutes, and PMS 40,000 KM dropped by 4 minutes. As well as the total cost that can be trimmed after kaizen is 3,720,000 rupiah.